Positive And Negative Emotion In Jenifer Lee’s Movie Script Frozen - Sumampow, Debora; Mamentu, Agustine C.; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The purpose of this investigation was to explore the emotional states portrayed in the film Frozen by Jenifer Lee. The scope of this research is specifically limited to examining the personality and feelings of Elsa, who serves as the central figure in the animated movie Frozen. While undertaking the analysis for this academic work, the writer concentrates exclusively on the research questions previously defined. The study gives prominence to Jennifer Lee's leading character, Elsa, with an emphasis on examining her nature and the emotions she undergoes. The selected method for this investigation is qualitative research, due to the fact that the gathered information exists as quotations and explanations. The details analysed in this research were extracted from the film Frozen by Jennifer Lee, which served as the primary material, and were supplemented with supporting information obtained from applicable materials like books, articles, and other resources that cover emotional experiences, functioning as supporting sources. The research identified Elsa's persona as being a powerful and inward-focused individual. This particular persona has a significant influence on the advancement of the plot and the evolution of other figures. Additionally, Elsa tends to respond to issues by steering clear, paying them no mind, and keeping her thoughts and feelings locked up inside, creating difficulties in controlling her emotional state. Subsequently, having established this portrayal, the aim of the author's study is to recognize and thoroughly understand the emotions represented by Elsa's character within the animated movie Frozen. Drawing on the findings, the writer reached the conclusion that the primary emotions that are apparent within her experience are positive emotions such as joy and contentment, as well as negative emotions such as dread, rage, and sorrow. Notably, Elsa's surrounding environment triggers each one of these feelings.